E-DIGITAL PROMOTION AND MARKETING PARIWISATA KOTIM MENGGUNAKAN METODE PUBLIC RELATION BERBASIS WEB - Riko Hidayat; Minarni (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2021)
Abstract: E-Digital Promotion and Marketing Tourism using the public relations method is a system that provides information about traditional cultural activities, history, and tourist service facilities in the form of lodging, motorcycle taxis, culinary, and souvenirs typical of East Kotawaringin. In this case, tourism in East Kotawaringin Regency does not yet have an information system that provides information on local wisdom in the form of tourist spots/locations, traditional culinary arts, historical traditional cultural activities and facilities that support the tourism sector. Also, the decreasing number of tourists who visit causes the need to increase promotion in the tourism sector. Therefore, the design of Tourism E-Digital Promotion and Marketing using the Public Relations method can make it easier for tourists to obtain information about East Kotawaringin Regency, especially tourists who want to visit East Kotawaringin Regency. Because, this method can maintain, manage, and maintain good relations between the organization and the community in order to increase effectiveness in the field of tourism promotion and marketing. Thus, the East Kotawaringin Regency Government can easily promote tourism, service providers or tourism products can market their products to visitors, and visitors can get complete and actual information about tourism in East Kotawaringin Regency.